Energy Pricing Strategy in Egypt - KANTOR Management Consultants (World Bank, Washington, DC, 2015)
The present report is the final deliverable of the consulting study, an energy pricing strategy for Egypt, undertaken for the Government of Egypt with World Bank financing. The purpose of the report is threefold: to provide an overview and summarize key aspects of the project, and integrate the main findings that have been presented in a series of separate reports developed during the project; to provide specific recommendations for energy prices and levels, the transition path to full cost-reflective prices and the mitigation support to accompany the pricing reform; and to provide an overview of the organizational arrangements and key actions for implementing the energy pricing strategy. The present report comprises of the following sections: section one gives introduction, section two provides an overview of key elements of the study, including its objectives and tasks, the rationale for reforming energy prices, and the methodology for determining cost-reflective prices and assessing the impact of implementing them. Section three contains the recommended energy prices over the suggested transition period, together with the subsidies that continue to apply during the transition, and proposals for modifying prices in accordance with movements in key price-determining parameters. Section four sets out the minimum levels of cash compensation that the authors recommend are provided to eligible households for the mitigation of negative impacts during the reform and transition period. Section five discusses the organizational arrangements for implementing, monitoring and evaluating the energy pricing strategy. The final section contains the action plan for implementing the strategy.